Avaliação da usinabilidade de cilindros para laminação de tiras a quente - Pernambuco, Luiz Rodrigo Alegre [UNESP] (2014)
The use of tests to evaluate the machinability of the material may be a determining factor in the viability of manufacturing processes, and contribute to planning the cost, time and in the search for the quality of the product through development of strategies and machining technologies. When the machined product is rolling mill roll, who played as a tool in the milling process the need for such development becomes clear when is examined the requirements for high performance rolling mill roll and identifies that they are the same requirements for high performance machining tools: wear resistance, toughness and hardness. So, this work proposes a machinability test in laboratory seeking the evaluation of two materials for rolling mill rolls: an indefinite chilled double poured cast iron and a microalloyed indefinite chilled double poured cast iron. The test was performed by milling with three edges of carbide on a machining center and the machinability analysis of this work was done by the criterion of end of life of the machining tool. The work found that the addition of alloying elements on the chemical composition of the rolling mill rolls directly influenced the machinability of microalloyed indefinite chilled double poured cast iron, because the volume fraction of carbides VC increased by almost three times in this material resulting in an abrasive wear on the edges of cutting tools